FORMER PARAMILITARY ORGANIZATIONS AS A PROXY FOR CIVIL DEFENSE: BOSNIA AND HERZEGOVINA AND LEBANON (Security Dialogues, 2023)
Lebanon and Bosnia and Herzegovina share many commonalities involvingsectarian and inter-ethnic strife, power-sharing agreement and the multitude of former andcurrent paramilitary and revolutionary organizations. In the greater political view, the rolesof paramilitary organizations are often controversial and problematic; however, during thetimes of civil-emergency, they often fill the niche of the missing first-responders. In Lebanon,a fragmented country, mired in an economic turmoil with occasional outbursts of sectarianviolence, the emergency response and assistance are severely curtailed, which was evident inthe sluggish response to the Beirut Port Explosion. In Bosnia and Herzegovina, a country miredin the continuous power-struggle among the nationalistic parties, the emergency responseis inefficient and fragmented. This paper examines the unique role of former revolutionaryorganizations in Beirut which have taken the form of de-facto civic organizations and formedthe backbone of emergency response, clean-up, and aid distribution. The study outlines severalexamples where the former revolutionary organizations mobilized and utilized their commandauthority, hierarchy, and community roles to provide an effective and sustainable emergencyresponse. In Bosnia, the study outlines the cases of community-based organization under thevestiges of the old general communal self-protection. The results indicate that the lessonslearned from the years of civil-strife in Lebanon and vestiges of communal-defence in Bosniahave contributed to the relief distribution, cooperation across the sectarian/ethnic lines andcoordination with external NGOs and state actors. Given the magnitude of the recent events(explosions and natural disasters), the role of civic organizations and their strategic approachto emergency response is instrumental to limiting further loss of life and deterioration of theoverall security situation.
Keywords: Emergency response, Civic Organization, Civil Defence, Communal Defence, Bosnia, Lebanon